(untitled) - COWI Consulting Engineers and Planners AS (Denmark, 1999)
This report provides a comprehensive and up-to-date statut on the current use of economic instruments in Danish environment protection. The report focuses on the implementation and enforcement aspects of the Danish experience.
Keywords: Environmental protection,Bảo vệ môi trường; Denmark,Đan Mạch